Respuesta :

The inverse function of f(x) is [tex]f^{-1}(x) = \sqrt[3]{x + 1} - 3[/tex]

How to determine the inverse function?

The function is given as:

f(x) = (x + 3)^3 - 1

Rewrite as:

y = (x + 3)^3 - 1

Swap x and y

x = (y + 3)^3 - 1

Add 1 to both sides

(y + 3)^3 = x +  1

Take the cube root of both sides

[tex]y + 3 = \sqrt[3]{x + 1}[/tex]

Subtract 3 from both sides

[tex]y = \sqrt[3]{x + 1} - 3[/tex]

Rewrite as:

[tex]f^{-1}(x) = \sqrt[3]{x + 1} - 3[/tex]

Hence, the inverse function of f(x) is [tex]f^{-1}(x) = \sqrt[3]{x + 1} - 3[/tex]

Read more about inverse function at:

https://brainly.com/question/2541698

#SPJ1